2009
DOI: 10.1167/iovs.08-2851
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Reduces Autophosphorylation of Retinal Insulin Receptor and Increases Protein-Tyrosine Phosphatase-1B Activity

Abstract: PURPOSE Protein-tyrosine phosphatase-1B (PTP1B) has been implicated in the negative regulation of insulin signaling. The expression, activity, and functional role of PTP1B in the retina are unknown. In this study, the authors examined the relationship between the retinal insulin receptor (IR) and PTP1B in normal and diabetic mouse retinas. METHODS IR and PTP1B localization was examined by immunohistochemistry. The activation of IR was analyzed using specific antibodies against phosphotyrosine. PTP1B activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 59 publications
5
51
0
Order By: Relevance
“…We expressed GST and various domains of Grb14 in bacteria and purified these fusion proteins. The purified fusion proteins were incubated with recombinant PTP1B and examined for the dephosphorylation of a synthetic phosphopeptide substrate (R RLIEDAE P YAARG) as a function of the PTP1B activity in vitro (35). A significant Grb14-mediated inhibition of PTP1B activity in vitro was found (Fig.…”
Section: Rpe65mentioning
confidence: 94%
“…We expressed GST and various domains of Grb14 in bacteria and purified these fusion proteins. The purified fusion proteins were incubated with recombinant PTP1B and examined for the dephosphorylation of a synthetic phosphopeptide substrate (R RLIEDAE P YAARG) as a function of the PTP1B activity in vitro (35). A significant Grb14-mediated inhibition of PTP1B activity in vitro was found (Fig.…”
Section: Rpe65mentioning
confidence: 94%
“…The IR, PI3K, and Akt pathway was found to be downregulated in diabetic retinopathy ( 132 ). Recently, we reported that diabetes downregulates IR activation and increases the activity of PTP1B ( 133 ).…”
Section: Protein Tyrosine Phosphatase-1b and Pi3k Pathwaymentioning
confidence: 94%
“…A few studies corroborate our results. VSMC isolated from mesenteric artery from WKY (Wistar Kyoto) and SHRSP (spontaneously hypertensive stroke prone rat) rats 48 and retinal from rats and mice 49 exposed to hyperglycemia present increased expression of the PTP, PTP1B, Protein carbonylation is a post-translational modification where carbonyl groups are introduced into proteins. It is considered a biomarker for oxidative stress-induced irreversible damage and leads to loss of protein function.…”
Section: Figure 2 High Glucose (Hg)-induced Reactive Oxygen Species mentioning
confidence: 99%